On Stochastic Models of Size Distributions - Shorrocks, A. F. (Review of Economic Studies, 1975)
Journal Article On Stochastic Models of Size Distributions Get access A. F. Shorrocks A. F. Shorrocks London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 4, October 1975, Pages 631–641, https://doi.org/10.2307/2296800 Published: 01 October 1975